Religious Experience as A Personal Guidance Base - Wahidin, Wahidin; Supriatna, Mamat (JOMSIGN: Journal of Multicultural Studies in Guidance and Counseling, 2019)
The relationship between religion and culture will shape personally, where the interaction of both is reflected through religious experience. The purpose of this study was to analyze the students' religious experiences at Ma'had Ali IAIN Salatiga in various cultures and ethnicities. The formulation of this study problem is how students' religious experiences in Ma'had Ali IAIN Salatiga are in different cultures and ethnicities? The research method used is qualitative method, with data collection technique in the form of questionnaire and interview. To analyze the data used content analysis, while the results of the study described in narrative-descriptive.